Effector repertoire of Phytophthora betacei : in search of possible virulence factors responsible for its host specificity (2021)
Phytophthora betacei is an oomycete plant pathogen closely related to Phytophthora infestans. It infects tree tomato (Solanum betaceum) in northern South America, but is, under natural conditions, unable to infect potatoes or tomatoes, the main hosts of its sister species P. infestans. We characterized, and compared the effector repertoires of P. betacei and other Phytophthora species. To this end, we used in silico approaches to predict and describe the repertoire of secreted proteins in Phytophthora species and determine unique and core effectors. P. betacei has the largest proteome and secretome of all Phytophthora species evaluated. We identified between 450 and 1933 candidate effector genes in P. ramorum, P. sojae, P. cactorum, P. parasitica, P. palmivora, P. infestans, and P. betacei genomes. The P. betacei predicted secretome contains 5653 proteins, 1126 of which are apoplastic effectors and 807cytoplasmic effectors.